Beliefs and Conservation of Palm-Leaf Manuscript Wraps in Nan Province - Suvannasiri (Homdok), Prabaidika Thanarat (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were 1) to study the characteristics of Palm-Leaf Manuscript Wraps patterns in Nan province, 2) to study the beliefs appearing in Palm-Leaf Manuscript Wraps in Nan province, and 3) to study guidelines for conservation of Palm-Leaf Manuscript Wraps in Nan province. This is a documentary research which employed the data analysis by means of descriptive content. The results of the research revealed that: 1) Characteristics of Palm-Leaf Manuscript Wraps in Nan Province, it was found that the cloth wrapping cloth in Nan province was rectangular. Materials used in weaving are cotton and silk threads, or cotton silk or silver silk, silk kham. Characteristics of the cloth wrapped in palm leaves are weaving with various techniques resulting in complex and uncomplicated patterns. 2) The principles of belief appearing in the pattern of Palm-Leaf Manuscript Wraps in Nan Province, it was found that the people of Nan Province had the belief in making scriptures to offer as an offering to the Lord Buddha. and help keep the scriptures for a long time There are 4 types of patterns on the fabric : 1. Animal prints are inspired by animals that actually exist in nature. 2. Flora designs are inspired by trees and flowers. hidden with the belief in fertility. 3. Patterns from Himmapan animals Caused by the introduction of animals that exist in beliefs. to apply weaving for prosperity. 4. Patterns from Buddhist beliefs. Beliefs that will help anchor the minds of the people in the community. 3) Guidelines for preserving Palm-Leaf Manuscript Wraps in Nan province. complete repair, system organization, use of conservation model with community communication process which uses a variety of communication channels through participation in the preservation of the Palm-Leaf Manuscript Wraps of people in Nan Province and the promotion of community culture learning from the wisdom of Palm-Leaf Manuscript Wraps in Nan province.